Risk factors for recurrence of endometrial hyperplasia in women of late reproductive and premenopausal age - С. М. Корниенко (Publishing House TRILIST, 2017)
According to many researchers, hyperplastic endometrial processes are not precancerous diseases. However, recurrent endometrial hyperplastic processes, as well as their combination with genital and extragenital pathologies, significantly increase the risk of malignant transformation of the endometrium. Late reproductive and premenopausal age is associated with an increase in the frequency of endometrial hyperplastic processes, extragenital pathology and operative interventions on the internal genitalia. The limited possibilities of conservative treatment in connection with concomitant diseases and the tendency of an increase in the recurring hyperplastic processes of the uterus make the problem of studying various aspects of hyperplastic endometrial processes in women of this age period extremely urgent. The purpose of research: to identify risk factors for recurrence of endometrial hyperplasia in women of late reproductive and premenopausal age. Materials and methods. We studied the clinical and medical history and long-term results of treatment of 276 women aged 35-54 years with endometrial hyperplastic processes. All patients underwent diagnostic and therapeutic hysteroscopic procedures were carried out. In 88 (31.9%) women for 1.5 years after treatment were observed relapses of the disease. These patients accounted for Рц group, the remaining 188 women included in the group K. Data processing was performed using variation statistics method, Mann-Whitney ranking test, χ2-test and Fisher's exact test. Results and conclusions. It should be noted the high rate of recurrence of endometrial hyperplastic processes in women of late reproductive and premenopausal age and lack of nosological specificity of recurrent endometrial hyperplastic processes. At the same time, recurrence of endometrial hyperplastic processes significantly increased the risks against the backdrop of giperpolimenorei, endometrioid disease, especially, adenomyosis and ovarian cysts. The greatest chances of recurrence were associated with the presence of patients extragenital diseases: gastrointestinal disorders, iron deficiency anemia, thyroid and breast cancer, vegetative-vascular dystonia. Within the framework of all investigated factors, the chances of recurrence of endometrial hyperplastic processes are most significant increased at the vegetative-vascular dystonia, and the pathology of the lacteal and thyroid gland.